The Bilateral Ovariectomy in a Female Animal Exacerbates the Pathogenesis of an Intracranial Aneurysm - Oka, Mieko (Brain Sci, 2020)
Considering the poor outcome of subarachnoid hemorrhage (SAH) due to the rupture of intracranial aneurysms (IA), mechanisms underlying the pathogenesis of IAs, especially the rupture of lesions, should be clarified. In the present study, a rat model of IAs in which induced lesions spontaneously ruptured resulting in SAH was used. In this model, the combination of the female sex and the bilateral ovariectomy increased the incidence of SAH, similar to epidemiological evidence in human cases. Importantly, unruptured IA lesions induced in female animals with bilateral ovariectomy were histopathologically similar to ruptured ones in the presence of vasa vasorum and the accumulation of abundant inflammatory cells, suggesting the exacerbation of the disease. The post-stenotic dilatation of the carotid artery was disturbed by the bilateral ovariectomy in female rats, which was restored by hormone replacement therapy. The in vivo study thus suggested the protective effect of estrogen from the ovary on endothelial cells loaded by wall shear stress. β-estradiol or dihydrotestosterone also suppressed the lipopolysaccharide-induced expression of pro-inflammatory genes in cultured macrophages and neutrophils. The results of the present study have thus provided new insights about the process regulating the progression of the disease.